Do Cookie Banners Respect My Browsing Privacy? Measuring the Effectiveness of Cookie Rejection for Limiting Behavioral Advertising - Mateo Ormeno; Ha Dao; Valeria Herskovic; Kensuke Fukuda (IEEE Access)
Online behavioral advertising (OBA) is a method within digital advertising that exploits web users’ interests to tailor ads. Its use has raised privacy concerns among researchers, regulators, and the media, emphasizing the need for a reliable mechanism to measure its prevalence. However, there is a lack of systematic research on how user consent choices affect OBA presence, and no open-source frameworks exist for large-scale automated OBA measurement. To address this, we design and implement OpenOBA, a new framework for automated OBA discovery on the web. OpenOBA is a general, modular, and scalable framework to support essentially any OBA measurement. With it, we conduct a study to measure the impact of three user consent choices for cookies on OBA, uncovering a complex online privacy landscape. We first confirm the presence of OBA by comparing the increased likelihood of encountering ads from a specific topic, i.e., Style & Fashion, when browsing with an artificially induced behavior versus when browsing without any particular behavior. Then, we find that the Accept All choice significantly raises the number of OBA ads. For the Reject All option, on the other hand, we observe that it reduces the number of unique third-party tracking cookie hosts (tracker domains) by around 70%, yet it still shows ads related to the user’s interests. Notably, we also find that OBA ads are only served through Google-related domains across the three banner interaction configurations used, despite the involvement of up to 191 different tracker domains in the Accept All configuration. This underscores the dominant role of major players in the OBA ad market. Finally, to foster reproducibility and further research, we open-sourced our framework and released all data and analysis scripts.